Investigating Patterns Of Distributed Leadership In Three Primary School Contexts In The Kingdom Of Bahrain - Jamali, Um Albaneen Yousif (2012)
Distributed leadership has stimulated a proliferation of theories and research studies in the last decades. The current paper explores the nature of distributed leadership as it relates to perspectives of formal leadership teams and other members of staff regarding areas of leadership and management and school culture. The research design of multiple case studies of three primary schools was selected for the purpose of the current study. The mixed method used cross-case analysis to investigate leadership as a distributed phenomenon in the participating schools. Data from interview transcripts, questionnaire and focus groups were used. Distributed leadership was indicated to be a common approach in the participating schools while patterns of distribution varied from one school context to another. On the other hand, various perspectives of formal leadership teams and other members of staff regarding areas of school leadership and culture demonstrated some challenges inherent in embedding a distributed culture within the school. The results indicated differences in beliefs regarding the importance of creating a learning culture as an integral element of distributed leadership, fear of challenge and disagreement and lack of awareness among members of staff regarding the complicated nature and patterns of distributed leadership. The study suggested that school culture requires further attention from policy makers, school leaders and researchers in the field.